Enhancing writing skill through writing process approach - M. Zaini Miftah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2015)
The study is aimed at developing the implementation of Writing Process Approach (WPA) to enhance the students’ skill in writing essay. The study employed Classroom Action Research. The subjects of the study were 15 university students enrolled in the writing class. The data were gained from writing task, observation and field notes. The findings show that the implementation of WPA with the proper model procedures developed can enhance the students’ skill in writing essay. Before the strategy was implemented, the percentage of the students achieving the score greater than or equal to C (56-70) was 40.00% (6 students of the class). However, after the strategy was implemented in Cycle I, it enhanced enough to 60.00% (9 students of the class), but this result did not meet the criteria of success set up in the study. Next, in Cycle II it increased slightly to 86.67% (13 students of the class). Thus, the enhancement of the students’ skill in writing essay can be reached but it should follow the proper model procedures of the implementation of WPA developed.